Cancer Drugs Fund requires further reform. (27th September 2016) - Grieve, Richard; Abrams, Keith; Claxton, Karl; Goldacre, Ben; James, Nicholas; Nicholl, Jon; Parmar, Mahesh; Parker, Chris; Sekhon, Jasjeet S; Smeeth, Liam; Spiegelhalter, David; Sculpher, Mark
Abstract : Reliance on "real world" observational data undermines evidence base for clinical practice